The Italo-African Institute - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Italo-African Institute was created at the initiative of a group of politicians and scholars at the beginning of this century. It is the oldest body in Italy concerned with cooperation with the African continent. The Institute includes a...